Land conversion subject of next Accomack meeting - Vaughn, Carol (Daily Times, 2008)
According to estimates in the updated plan, the county will add 7,900 to 15,300 new people by 2030 due to outside growth pressures, requiring 2,000 to 5,000 additional acres of land to be converted to residential and civic uses.